2017
DOI: 10.7196/ajhpe.2017.v9i3.691
|View full text |Cite
|
Sign up to set email alerts
|

Radiation safety requirements for training of users of diagnostic X-ray equipment in South Africa

Abstract: Having provided an international perspective, it is important to consider the local scenario. The South African (SA) Department of Health (DoH) accepted the recommendations of the ICRP and regulates radiation protection within the framework of the Hazardous Substances Act No. 15Background. Globally, the aim of requirements regarding the use and ownership of diagnostic medical X-ray equipment is to limit radiation by abiding by the 'as low as reasonably achievable' (ALARA) principle. The ignorance of radiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Specific comments confirmed the importance to record evidence of mastery of content by means of assessment. The importance of distributing the workload between the years of study and repetition to provide students with the opportunity to reach a high level of understanding was emphasised (Van der Merwe et al 2017).…”
Section: Collaboration By Means Of a Delphi Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Specific comments confirmed the importance to record evidence of mastery of content by means of assessment. The importance of distributing the workload between the years of study and repetition to provide students with the opportunity to reach a high level of understanding was emphasised (Van der Merwe et al 2017).…”
Section: Collaboration By Means Of a Delphi Surveymentioning
confidence: 99%
“…
CUT) as radiation workers. Therefore, the content and assessment of a course for radiation safety regulations were investigated and determined by a panel of experts in the field using a Delphi process (Van der Merwe 2015). The course was divided into learning units and included in the new bachelor's degree at the CUT, with the first roll-out of the first year in 2014.
…”
mentioning
confidence: 99%
“…However, despite radiation protection inclusion throughout South African radiography education curricula 1 and being mandated, there is testament to contrary clinical practices in South Africa. 2,3 The Health Professions Act, 1974 (act no. 56 of 1974) 4 defines radiation protection as: "the application of radiation protection measures and techniques to minimise radiation exposure to patients, staff, self, and the public in accordance with the rules, regulations, and recommendations of the Radiation Control Directorate of the National Department of Health in South Africa and to ensure the health, safety and wellbeing of staff."…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in Gauteng, South Africa, revealed that only 33% of radiographers knew the function of exposure indicators 8 and a quarter of patients received more radiation exposure than was necessary to produce a diagnostic radiograph 9 . However, the reasons for South African radiographers’ radiation protection behaviour remains largely unexplored 7,8,10–12 . The theory of planned behaviour posits that behaviour depends mostly on the intention to perform a behaviour 13 .…”
Section: Introductionmentioning
confidence: 99%